2013
DOI: 10.2166/wp.2013.105
|View full text |Cite
|
Sign up to set email alerts
|

Tapped out: how can cities secure their water future?

Abstract: Cities around the world are struggling to access additional water supplies to support their continued growth because their freshwater sources are becoming exhausted. Half of all cities with populations greater than 100,000 are located in water-scarce basins, and in these basins agricultural water consumption accounts for more than 90% of all freshwater depletions. In this paper we review the water development histories of four major cities: Adelaide, Phoenix, San Antonio and San Diego. We identify a similar pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 107 publications
(58 citation statements)
references
References 32 publications
1
53
0
3
Order By: Relevance
“…In fact, half of all cities with populations greater than 100,000 are located in water-scarce basins. In these basins, agricultural water consumption accounts for more than 90 % of all freshwater depletions (Hunger and Döll 2008;Richter et al 2013). In a critical analysis, Richter et al (2013) point out that nearly all water used for domestic and industrial purposes is eventually returned to a water body.…”
Section: Water Challenges In the Citymentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, half of all cities with populations greater than 100,000 are located in water-scarce basins. In these basins, agricultural water consumption accounts for more than 90 % of all freshwater depletions (Hunger and Döll 2008;Richter et al 2013). In a critical analysis, Richter et al (2013) point out that nearly all water used for domestic and industrial purposes is eventually returned to a water body.…”
Section: Water Challenges In the Citymentioning
confidence: 99%
“…In these basins, agricultural water consumption accounts for more than 90 % of all freshwater depletions (Hunger and Döll 2008;Richter et al 2013). In a critical analysis, Richter et al (2013) point out that nearly all water used for domestic and industrial purposes is eventually returned to a water body. For instance, toilets are flushed and purified wastewater as well as cooling water in power plants is often returned to rivers.…”
Section: Water Challenges In the Citymentioning
confidence: 99%
See 1 more Smart Citation
“…Such a transition would reconceive water infrastructure in terms of the water-related services provided rather than the quantity of water delivered [Fuenfschilling and Truffer, 2013;Wolff and Gleick, 2002]. Previous research on water-stressed cities has found that after exhausting local sources of ground and surface water, cities generally turn to water importation (usually from more distant surface water sources via aqueducts) and then to groundwater storage, desalinization (if the city is near a saltwater source or has access to brackish groundwater), and water conservation [Richter et al, 2013]. Thus, water conservation is often part of a general transition of water regimes in response to water stress, but it is of particular interest because it is a low-cost option that has diverse environmental benefits, including energy conservation.…”
Section: Introductionmentioning
confidence: 99%
“…The strategies California has used historically to address these challenges are reflected in the Richter et al study [4]. Surface water and groundwater are fully, if not over, allocated (Strategy #1).…”
Section: California's Diversifying Water Supply MIXmentioning
confidence: 99%